Prevalence and factors associated with mental distress among men at higher risk of HIV infection enrolled in an HIV pre-exposure prophylaxis program in Tanga, Tanzania - Kitomary, Nuruel Robert; Metta, Emmy; Leshabari, Melkizedeck T.; Moen, Kåre; Mmbaga, Elia J. (Frontiers in Psychiatry, 2026)
BackgroundData on the extent of mental health among men who have sex with men (MSM) in Tanzania are scarce, but studies elsewhere report a high prevalence of mental distress, mainly depression and anxiety symptoms. Mental distress has been linked to stigma, rejection, violence, and inadequate social support, with increased HIV vulnerability and poor uptake of preventive interventions such as pre-exposure prophylaxis (PrEP) and antiretroviral treatment. This study aimed to determine the prevalence of and factors associated with mental distress among men who have sex with men on PrEP in Tanga, Tanzania.MethodsThis paper is based on data emanating from the control arm of a pragmatic quasi-experimental trial for HIV PrEP rollout in Tanzania with registration number MUHAS-REC-12-2024–2542 accordingly. The study population included men aged 18 years or older initiating PrEP. Participants were recruited through respondent-driven sampling (RDS). Mental distress was assessed at baseline using the Patient Health Questionnaire - two-question version (PHQ-2) and Generalized Anxiety Disorder - two-question version (GAD-2) for depressive and anxiety symptoms, respectively. A modified Poisson regression model was used to determine independent factors associated with mental distress.ResultsOur study found that 16.8% of MSM on PrEP experienced mental distress. Factors associated with higher prevalence of mental distress included high self-perceived HIV risk (aPR=2.29, 95% CI = 1.14–4.59, p=0.020), low PrEP knowledge (aPR=2.7, 95% CI = 1.29–5.64, p=0.020), and high PrEP stigma (aPR=1.65, 95% CI = 1.03–2.64, p=0.036). Participants reporting to access condoms easily had a lower prevalence of mental distress (aPR=0.57, 95% CI = 0.35–0.94, p=0.028).ConclusionsMental distress was relatively high among MSM, especially those with low PrEP knowledge, high PrEP stigma, and perceived high HIV risk, while easy condom access lowered the prevalence. Healthcare stakeholders should work to enhance PrEP awareness, reduce stigma, and ensure condom availability. Expanding and integrating mental health services within HIV programming is crucial in achieving the goal of ending the HIV epidemic by 2030.